2013
DOI: 10.3109/13880209.2013.794364
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic activity ofKalanchoe pinnatain streptozotocin-induced diabetic rats by glucose independent insulin secretagogue action

Abstract: The DCM fraction of Kalanchoe pinnata demonstrates excellent insulin secretagogue action and can be useful in treatment of diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 25 publications
0
14
0
3
Order By: Relevance
“…It was reported that Korean red ginseng had a beneficial effect on the treatment of diabetes by stimulating insulin secretion by its own [ 36 ]. In addition, a phenyl alkyl ether derivative isolated from the Kalanchoe pinnata leaves showed insulin secretagogue action in glucose independent manner, which could be useful in treatment of diabetes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that Korean red ginseng had a beneficial effect on the treatment of diabetes by stimulating insulin secretion by its own [ 36 ]. In addition, a phenyl alkyl ether derivative isolated from the Kalanchoe pinnata leaves showed insulin secretagogue action in glucose independent manner, which could be useful in treatment of diabetes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extract has shown smooth muscle relaxing properties [ 18 , 19 ]. Other extracts from the Bryophyllum family than Kalanchoe pinnata have shown anti-diabetic activity [ 20 ] and anti-inflammatory effects [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The plant I. gracilis may, therefore, behave in a similar manner as plants which possess insulin secretagogue compounds such as Kalanchoe pinnata Lam. (Crassulaceae), Momordica charantia L. (Cucurbitaceae), and Trigonella foenum graecum L. (Fabaceae) (Patil et al, 2013;Shah et al, 2006;Yibchok-Anun et al, 2006). The presence of the antioxidants flavonoids and other polyphenols in the 80% methanolic extract of I. gracilis was observed and is probably the reason why the free radical DPPH was effectively scavenged.…”
Section: Discussionmentioning
confidence: 98%